2019
DOI: 10.1038/s41598-019-40968-x
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled and ATP-sensitive inwardly rectifying potassium ion channels are essential for HIV entry

Abstract: The high genetic diversity of Human Immunodeficiency virus (HIV), has hindered the development of effective vaccines or antiviral drugs against it. Hence, there is a continuous need for identification of new antiviral targets. HIV exploits specific host proteins also known as HIV-dependency factors during its replication inside the cell. Potassium channels play a crucial role in the life cycle of several viruses by modulating ion homeostasis, cell signaling, cell cycle, and cell death. In this study, using pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…In addition to azithromycin, our study found other antibiotics, including teicoplanin, anisomycin (Dyall et al, 2014), valinomycin (Dubey et al, 2019), which demonstrated anticoronavirus functions in vitro and/or in vivo (Table 1) well (Zhou et al, 2016). Valinomycin is a K + ionophore that can change the membrane potential by conducting ions directly through membrane.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition to azithromycin, our study found other antibiotics, including teicoplanin, anisomycin (Dyall et al, 2014), valinomycin (Dubey et al, 2019), which demonstrated anticoronavirus functions in vitro and/or in vivo (Table 1) well (Zhou et al, 2016). Valinomycin is a K + ionophore that can change the membrane potential by conducting ions directly through membrane.…”
Section: Discussionmentioning
confidence: 85%
“…It can treat B. gibsoni, a species of bacterial infection, by changing bacteria's cellular cation concentration in vitro (Yamasaki et al, 2009). In a study, TZMbl cells were treated with valinomycin before HIV infection, and valinomycin at 10 nM concentration impeded HIV entry to TZMbl cells by nearly 50% (Dubey et al, 2019). The study also showed that valinomycin inhibits HIV entry by increasing the membrane depolarization, which indicates membrane polarization is crucial for HIV entry.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work also highlights a requirement for K + channels during human immunodeficiency virus (HIV) infection. Using pharmacological approaches ( Figure 1 A) [ 40 ] HIV entry could be blocked with ifenprodil and the broad spectrum K + channel blocker tetraethylammonium (TEA). Khan et al also showed that the pharmacological activation of the endolysosome-resident transient receptor potential mucolipin 1 channel (TRPML1) enhanced the degradation of HIV-Tat (a multi-function viral protein involved in transcription, splicing, capping, and translation), which in turn reduced the transition from viral latency [ 52 ].…”
Section: Ion Channels Involved In Viral Entrymentioning
confidence: 99%
“…Emerging studies suggest that the current description of virus entry processes involving acidification alone are too simplistic and that the accumulation of other ions including K + and Ca 2+ influence virus trafficking (3843). In the context of PyV infection, Ca 2+ ions have been shown to affect the structure and organisation of virus particles, regulating their disassembly through virion swelling (40, 4446).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of PyV infection, Ca 2+ ions have been shown to affect the structure and organisation of virus particles, regulating their disassembly through virion swelling (40, 4446). However, despite the evidence that cellular ion channels are targeted by a wide range of viruses to enhance specific lifecycle stages, their role during PyV entry has not been defined (40, 41, 53, 42, 43, 4752).…”
Section: Introductionmentioning
confidence: 99%